ANALISIS WACANA EDUKASI DAN KONTROVERSI DALAM KONTEN TIKTOK dr. Richard Lee: KAJIAN DENGAN MODEL AWK VAN DIJK - Sarma Panggabean; Desi Natalia Br Ginting; Tarihoran, Yuly; Novia Satna Br Ginting; Ardina Therecia Sitepu (CV MUARA EDUKASI, 2025)
The development of social media has made TikTok an important space for shaping public opinion, disseminating information, and practicing digital education. One public figure who actively uses this platform is Dr. Richard Lee, a cosmetic doctor known for his educational content and criticism of illegal skincare products. His assertive, forthright, and straightforward communication style often causes controversy while strengthening his image as an honest and courageous doctor. This study aims to analyze how educational discourse and controversy are constructed in Dr. Richard Lee's TikTok content using Teun A. van Dijk's Critical Discourse Analysis (CDA) model. The study was conducted by analyzing the text structure, social cognition, and social context of a number of relevant TikTok videos. The results show that educational discourse is constructed through the affirmation of scientific values, the use of evidence, and an informative style of language, while controversial discourse emerges through sharp criticism, the use of emotional diction, and expressions of rejection of cosmetic industry practices that are considered harmful to society. In addition, the discourse of authenticity is also evident through claims of impartiality and transparency in every product review. Overall, this discourse shows that language in social media functions as a means of education, resistance, and self-image formation.